The effect of crime and safety program on tourist travel intention in Malaysia - Nur Farah Hanis Jalalol Khaizi; Nur Dy’anna Nordin; Zainoor Sabrina Zainul Hisham; Joanna Ng Row Yee (2021)
The purpose of this research is to identify the effect of planned crime, opportunistic crime and the improvement of safety program on tourist intention to travel. Planned crime, opportunistic crime, and safety planning are the focus of many decision-making processes and destination selection models, which highlight the travel factor. It plays an important role in establishing destination awareness and influencing travel intentions. This survey has been distributed to 384 respondents in Malaysia through non-probability sampling by using Google form. The data was analyzed by using SPSS and was tested using descriptive analysis, reliability analysis using Cronbach’s Alpha Rule of Thumb and correlation test. The result revealed that planned crime, opportunistic crime and safety program influence tourist travel intention.